INTEGRATING TECHNOLOGY IN LEARNING IN MADRASAH: TOWARDS THE DIGITAL AGE - Mukti Ali; M. Anwar Aini; Sitti Nur Alam (Indonesian Journal of Education (INJOE), 2024)
Madrasas have a crucial role in providing a strong foundation for individual development and societal progress. Madrasas have an important role in teaching critical skills and information literacy. In this digital age, information is abundant and easily accessible to anyone. Madrasas in the digital age must encourage creativity and collaboration. Optimizing learning by integrating technology is something that millennial teachers hope to implement. By utilizing information technology and integrating it in learning, it will make it easier for teachers to convey knowledge. Apart from that, learning can be more fun and interactive. In facing the challenges of the digital age, madrasas have an important role in preparing future generations and fueling the spirit of innovation. One of the main challenges facing madrasas in the digital age is the digital divide among students. Not all students have access to the necessary technology or internet connection outside the madrasah environment. This research is a library study research, by looking at literary sources, books, notes, and various reports related to the problem to be solved. This research discusses the importance of integrating technology in education, the challenges faced by madrasas in adopting technology for learning, and the importance of facing the digital age in madrasas.